The Visualization of the Chinese Economy from A Multi-dimensional Perspective: 1979-2009 - Estrada, Mario Arturo Ruiz; Yeoh, Emile Kok-Kheng (WILAYAH: The International Journal of East Asian Studies, 2011)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.